Pengaruh Lama Perendaman Terhadap Karakteristik Infused Water Jeruk Limau (Citrus amblycarpa (Hassk.) Ochse) - Abielius Sugiardja, Bernard; Kartika Pratiwi, I Desak Putu; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 3 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i03.p05, 2022)
This study aimed to determine the effect of immersion time on the characteristics of lime infused water and to determine the appropriate immersion time to produce lime infused water with the best characteristics. The method used in this study was a completely randomized design with treatment of immersion time that consistsed of 5 levels: 3 hours, 6 hours, 9 hours, 12 hours and 15 hours. The experiment was repeated in three replications to obtain 15 experimental units. The data were analyzed using Analysis of Variance (ANOVA) and if there was a significant effect of treatment on the observed variables, the Duncan Multiple Range Test (DMRT) were performed. The results showed that the treatment of immersion time had significant effect on turbidity level, degree of acidity (pH), total phenol, total flavonoid, vitamin C, antioxidant activity, aroma, color, taste and overall acceptance. The best treatment was 12 hours with 0.11 (OD600) of turbidity level, 4.29 degree of acidity (pH), 68.70 mg GAE/100 ml of total phenol, 22.70 mg QE/100 ml of total flavonoids, 8.10 mg/100 ml of vitamin C, 82.34% of antioxidant activity and 11793.46 mg/L of IC50, aroma liked, color liked, taste liked and overall acceptance liked.